The influence of intensive nutritional counseling in Posyandu towards the growth 4-18 month old children - Noviati Noviati; J C Susanto; H Selina; M Mexitalia (Indonesian Pediatric Society, 2006)
Introduction Under 5 years is a critical period for child growth,when growth faltering often occurs. Periodical growth monitoringand nutritional counseling can detect growth faltering earlier, de-termine the cause, and find alternatives to solve such problems.Objective To determine the benefit of nutritional counseling onknowledge, attitude, practice of mothers, and child growth.Methods A randomized controlled trial was conducted inSendangguwo, Semarang on 143 children of the treatment groupand 135 children of the control group. Nutritional counseling wasgiven to mothers in the treatment group by trained health volun-teers. Changes of weight for age Z-score (WAZ), height for age Z-score (HAZ), and weight for height Z-score (WHZ) were analyzedrepeatedly by using ANOVA. The differences of Î”WAZ, Î”HAZ, andÎ”WHZ between groups were compared by student t-test. GEE (gen-eralized estimating equation) analysis was used to analyze theeffect of confounding variables on the changes of WAZ.Results After 6 months of counseling, knowledge, attitude, andpractice of nutrition in the treatment group significantly increasedcompared to that of the control group (P<0.001). The WAZ, HAZ,and WHZ curves in the control group decreased. However, in thetreatment group, WHZ increased and there was stabilization ofWAZ. At the end of the study, treatment group had significantlyimproved their WAZ (P<0.001), HAZ (P=0.004), and WHZ(P<0.001) compared to that of the control group.Conclusion Nutritional counseling can improve knowledge, atti-tude, and practice of mothers, and has beneficial effects on childgrowth by WAZ, HAZ, and WHZ